New approach on the bioconversion of vineyard pruning waste into surface-active compounds by Lactobacillus paracasei - Vecino, X. (2015)
Strategic funding of UID/BIO/04469/2013 unit and project ref RECI/BBB-EBI/0179/2012 (project number FCOMP-01-0124-FEDER-027462) and Xanel Vecino post-doctoral grant (ref SFRH/BPD/101476/2014) funded by Fundação para a Ciência e a Tecnologia, Portugal